2013
DOI: 10.4049/jimmunol.1300270
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Amniotic IL-1β Induces Fetal Inflammation in Rhesus Monkeys and Alters the Regulatory T Cell/IL-17 Balance

Abstract: Very low birth weight preterm newborns are susceptible to the development of debilitating inflammatory diseases, many of which are associated with chorioamnionitis. To define the effects of chorioamnionitis on the fetal immune system, IL-1β was administered intra-amniotically at ∼80% gestation in rhesus monkeys. IL-1β caused histological chorioamnionitis as well as lung inflammation (infiltration of neutrophils or monocytes in the fetal airways). There were large increases of multiple pro-inflammatory cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 71 publications
8
77
0
Order By: Relevance
“…In this regard, we previously demonstrated that the posterior mediastinal lymph node responds with a doubling of weight and increased trafficking of activated neutrophils and monocytes as a result of intrauterine lung inflammation (20). We recently demonstrated that IA LPS injection decreased Tregs and increased IL-17-producing cells in the posterior mediastinal lymph node of fetal rhesus macaques (22). Interestingly, these profound changes in the local lymph nodes were not paralleled by changes in the blood cells, showing compartmentalization of the FIRS responses after chorioamnionitis.…”
Section: Discussionmentioning
confidence: 98%
“…In this regard, we previously demonstrated that the posterior mediastinal lymph node responds with a doubling of weight and increased trafficking of activated neutrophils and monocytes as a result of intrauterine lung inflammation (20). We recently demonstrated that IA LPS injection decreased Tregs and increased IL-17-producing cells in the posterior mediastinal lymph node of fetal rhesus macaques (22). Interestingly, these profound changes in the local lymph nodes were not paralleled by changes in the blood cells, showing compartmentalization of the FIRS responses after chorioamnionitis.…”
Section: Discussionmentioning
confidence: 98%
“…Current hypotheses suggest that an imbalance between CD41 Tregs and Th17 cells, T cells with opposing actions, underlies the pathophysiology of immune diseases, 68 inflammatory processes, 69 and pregnancy pathologies such as PTB. 70 Indeed, there is an increase of Th17 cells in the chorioamniotic membranes from women who underwent preterm labor with acute chorioamnionitis. 44 Our results did not support this hypothesis at the maternal-fetal interface since no changes were observed in uterine Th1, Th17, or Th9 cells prior to LPS-induced PTB.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size for statistical calculations was determined by use of the maximum number of unique biological replicates available. All experiments were performed two or more times with distinct biological samples (total of [8][9][10][11][12]. Each individual experiment contained a minimum of 4 ABM and 4 FBM samples.…”
Section: Statisticsmentioning
confidence: 99%
“…4 In contrast, production of inflammatory cytokines (eg, interferon-g [IFN-g], interleukin-6 [IL-6], tumor necrosis factor a, and IL-1) in response to bacterial infection characterizes the fetal inflammatory response syndrome (FIRS), which is associated with spontaneous abortion or preterm labor. [5][6][7][8][9][10] The fetal immune system actively contributes to tolerance of maternal antigens. 1,11 Upon stimulation with noninherited maternal alloantigens, fetal naïve CD4 1 T cells preferentially differentiate into…”
Section: Introductionmentioning
confidence: 99%